2017
DOI: 10.1088/1361-6552/aa6d2b
|View full text |Cite
|
Sign up to set email alerts
|

Charging a capacitor with a photovoltaic module

Abstract: Charging a capacitor with a photovoltaic module is an experiment which reveals a lot about the modules characteristics. It is customary to represent these characteristics with an equivalent circuit whose elements represent its physical parameters. The behavior of a photovoltaic module is very similar to that of a single cell but the electric energy involved is much higher, which represents a major challenge for their characterization. In this work, an experiment is conducted to test out this behavior and in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
2
Order By: Relevance
“…In fact, experiments have shown that V c increases linearly in the early stage of the charging. However, at later stage of charging, the V c curve resembles the behavior of the circuit charged by battery, and starts to level off when approaches the output voltage limit of solar cells [4]. A Van de Graaff generator was used as a constant current source to charge capacitors, and V c was observed to strictly follow the linear behavior [5].…”
Section: The Most Energy Efficient Way To Charge the Capacitor In A R...mentioning
confidence: 99%
“…In fact, experiments have shown that V c increases linearly in the early stage of the charging. However, at later stage of charging, the V c curve resembles the behavior of the circuit charged by battery, and starts to level off when approaches the output voltage limit of solar cells [4]. A Van de Graaff generator was used as a constant current source to charge capacitors, and V c was observed to strictly follow the linear behavior [5].…”
Section: The Most Energy Efficient Way To Charge the Capacitor In A R...mentioning
confidence: 99%
“…The method of using variable resistors is often simple to implement [71] but poses difficulties with accuracy, resolution, sweep speed, and scalability [70,77]. Capacitive loads serve as a more practical option for scalable rapid measurements [78][79][80][81][82][83][84][85]. The capacitive loads must be designed for specific sizes, which may cause this technique to suffer in scalability and cost, without the flexibility to measure larger system sizes.…”
Section: I-v Curve Tracersmentioning
confidence: 99%
“…In [28], a genetic algorithm based on a bee colony is used to obtain the parameters of a PV cell after plotting its I-V curve with a capacitive tracer. In [29], [30], [31], and [32], the operation of this type of tracer, and different methods of connecting the capacitor, are discussed.…”
Section: Capacitive Load Tracermentioning
confidence: 99%